Comparison of Laser Scanning Diagnostic Devices for Early Glaucoma Detection. Issue 6 (August 2015) - Schulze, Andreas; Lamparter, Julia; Pfeiffer, Norbert; Berisha, Fatmire; Schmidtmann, Irene; Hoffmann, Esther M.
Abstract : Background: To compare the diagnostic accuracy and to evaluate the correlation of optic nerve head and retinal nerve fiber layer thickness values between Fourier-Domain optical coherence tomography (FD-OCT), confocal scanning laser ophthalmoscopy (CSLO), and scanning laser polarimetry (SLP) for early glaucoma detection. Patients and Methods: Ninety-three patients with early open-angle glaucoma, 58 patients with ocular hypertension, and 60 healthy control subjects were included in this observational, cross-sectional study. All study participants underwent FD-OCT (RTVue-100), CSLO (HRT3), and SLP (GDx VCC) imaging of the optic nerve head and the retinal nerve fiber layer. Area under the receiver operating characteristic curves (AUROC) and Bland-Altman analysis were performed. Results: The parameters with the highest diagnostic accuracy were found for FD-OCT cup-to-disc ratio (AUROC=0.841), for SLP NFI (AUROC=0.835), and for CSLO cup-to-disc ratio (AUROC=0.789). Diagnostic accuracy of the best CSLO and SLP parameter was similar ( P =0.259). There was a small statistically significant difference between the best CSLO and FD-OCT parameters for differentiating between glaucoma and healthy eyes ( P =0.047). Conclusions: FD-OCT and SLP have a similarly good diagnostic ability to distinguish between early glaucoma and healthy subjects. The diagnostic accuracy of CSLO was comparable with SLP and marginally lower compared with FD-OCT.